(untitled) (Heritage, 2024)
In the enclosure of the paper, we bring the testimony about the Serbs’ suffering in Kosovo and Metohia, namely in certain villages in municipalities Vučitrn, Lipljan, Kosovo Polje and Priština. The document is stored in the archives of the Eparchy of Raška Prizren, which has been relocated from Prizren to the Gračanica Monastery since 1999.